An analysis on the enforcement of community service order as punishment for the child offenders in Malaysia / Ainul Mardhiah Razlan …[et al.] - Razlan, Ainul Mardhiah; Ya'acop, Nur Izyan; Anwar, Noor Liyana; Sofian Gan, Norsheila (2014)
The order of community service is laid down in several relevant statutes which provide it as one of the alternative punishment to imprisonment in the framework of Malaysian criminal justice system. However, due to the lacuna in the legislation namely Child Act 2001, the community service is not successfully applied on child offenders in Malaysia. Besides, it is not clearly stated or specifically provided in the statute regarding community service order (CSO) as one of the punishment for child offender. In fact, the existence of organisation that regulates community service does not give any effect as the punishment is at the discretion of the judge to decide. This study consists of five chapters which focus on analyzing the procedures, duration and scope of work in community service, examine the forms of punishments provided in Child Act 2001 and whether it includes CSO. Moreover, this study is done to analyse the advantages of having CSO as a form of punishment for child offenders in Malaysia and lastly to propose the inclusion of community service as a form of punishment in Child Act 2001 in the event of any lacuna. A lot of research findings and critical views collected to be the basis of suggestions and recommendations to overcome the problem arise. This study shows that CSO is an ideal punishment to minor offences committed by child offender and should be clearly incorporated into Child Act 2001. This order has a lot of advantage as compared to other types of punishment.